CAUSES OF MORTALITY IN INDIVIDUALS WITH TUBEROUS SCLEROSIS COMPLEX (TSC). Issue 12 (15th November 2016) - Amin, Sam; Lux, Andrew; Calder, Nuala; Laugharne, Matthew; Osborne, John; O'Callaghan, Finbar
Abstract : Objectives: The causes of death in this group of patients have rarely been studied with the one published account from the Mayo Clinic appearing in 1991. We aimed to investigate mortality in a large clinical cohort of TSC patients to see whether causes of mortality have changed over time or differ within a different healthcare system. Methods: We have identified 284 patients from our database at the Bath TSC clinic with a definite diagnosis of TSC who have attended the clinic from 1981 to the present day. We reviewed the medical records including medical notes, radiology images, and if applicable, death certificates and post-mortem reports. Results: 16 died secondary to complications of TSC: eight from TSC kidney related complications; four from SUDEP; two from lymphangioleiomyomatosis; one secondary to a subependymal giant cell astrocytoma; and one from a pancreatic malignancy. The median age of death was 33 years (IQR 26–46). Mortality was significantly more common in the learning difficulty group. Conclusion: SUDEP is a significant cause of mortality. This study has shown that LD patients are at significantly greater risk of early mortality and thus implies the need for greater vigilance for TSC related complications in this patient group.